Solving Pixel Puzzle Using Rule-Based Techniques and Best First Search - Dina Stefani; Arnold Aribowo; Kie Van Ivanky Saputra; Samuel Lukas (International Conference on Engineering and Technology Development (ICETD), 2012)
Pixel puzzle is a logic puzzle which consists of a blank grid with clues on the left of every row and on the top of every column. The objective is to paint blocks in each row and column so their length and sequence corresponds to the clues, and there is at least one empty square between adjacent blocks. There are many possible solutions to paint blocks in each row and column. Solving the puzzle manually gives the possibility to fill cells yield erroneously. Therefore an attempt to solve the puzzle with the aid of computer software is performed.In this paper, ruleâbased techniques and best-first search are utilized to solve the puzzle. According to experiments have been conducted, it can be concluded that rule-based techniques and best-first search are able to solve the Pixel Puzzle. The result also indicates that the larger size of pixel puzzle, the longer average time to solve is needed. Moreover, the average time to solve one cell of pixel puzzle depends on the size itself except for the 10 Ã 10 and 15 Ã 15 pixels.